Who am i? the cultural identity of teenages - Wong, S.L. (2015)

(untitled)
Identity is a person's conception and expression of their individuality or group affiliations such as national identity or cultural identity. In general, cultural groups differ based on their members' beliefs, values and norms, or behavior patterns. Nonetheless, language is a main component of cultural identity. This study aims to find out the views and perceptions of the secondary students on Chinese language, Chinese cultural values, and preservation and transmission of cultural traditions.